The relationship between authors and main thematic categories in the field of knowledge organization: a bibliometric approach - Arboit, Aline Elis; Gracio, Maria Cláudia Cabrini; Oliveira, Ely Francina Tannuri de; Bufrem, Leilah Santiago (Ergon-verlag Gmbh, 2012)
This is a study about the relationships between authors and the main thematic categories in the papers published in the last five International ISKO Conferences, held between 2002 and 2010. The aim is to map the domain as ISKO conferences are considered the most representative forum in the field. The published papers are considered to indicate the relationships between authors and themes. The Classification Scheme for Knowledge OrganizationError! Bookmark not defined. Literature (CSKOL) was used to categorize the papers. The theoretical and methodological foundations of the study can be found in the concept of domain analysis proposed by Hjørland. The analysis of the papers (n = 146) led to the identification of the most productive authors, the networks representing the relationships between the authors as also the categories that constitute the primary areas of research.